Optimal seed mixtures and seeding rates for restoration of surface disturbances on Colorado shortgrass steppe - Barr, Stephanie, author; Paschke, Mark, advisor; Meiman, Paul, committee member; Brummer, Joe, committee member; Jonas, Jayne, committee member (Colorado State University. Libraries, 2013)
The discovery of oil and gas resources over the last decade has led to unprecedented localized and dispersed surface disturbances on shortgrass steppe ecosystems in the western US. Reclaiming and restoring these surface disturbances to native ecosystems through revegetation seeding has proven challenging. Seed mixes and rates currently used are generally similar across private and public sectors (3-10 species at rates ranging from 400-600 pure live seeds (PLS) m-2 broadcast seeded). The objective of this study was to determine an optimal seed mix diversity level and corresponding seeding rate for restoration of surface disturbances in shortgrass steppe. I examined five seed mix diversity levels, 5-50 species, and five seeding rates, 400-1600 PLS m-2 using a response surface regression experimental design at twelve sites. Treatments and overall restoration success were evaluated based on resulting biomass and diversity of seeded, volunteer native, noxious, and non-native species, and the density of seeded species. Results show greatest restoration success occurring during year one at a seed mix diversity level of 43 species and a seeding rate of 1229 PLS m-2, and during year two at a diversity level of 42 species and a rate of 932 PLS m-2. These results suggest that higher seed mix diversity levels and higher seeding rates could lead to greater restoration success for surface disturbances in shortgrass steppe.
Keywords: restoration success; shortgrass steppe; seed mix diversity; seeding rate